PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT PENJUALAN OBJEK JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN - Roida Nababan (LPPM Universitas HKBP Nommensen, 2021)
Based on the discussion, it can be seen that The legal arrangements in the financing agreement with fiduciary guarantees are subject to the Civil Code in accordance with the conditions for the validity of the agreement. Article 1319, Article 1320 and Article 1338 are followed as well as the provisions in Presidential Decree 61 of 1988 concerning Financing Institutions and Presidential Regulation no. 9 of 2009 concerning Financing Institutions. Legal protection for consumers due to the sale of the object of a fiduciary guarantee in a financing agreement is that it must not violate the principle of consumer protection as well as provide legal certainty and provide legal protection for interested parties and guarantees, especially related to consumer rights and the sale of objects that are objects of the fiduciary guarantee agreed by fiduciary giver and receiver. The judge's legal considerations in the Supreme Court of the Republic of Indonesia Number 441 K/Pdt.Sus-BPSK/2019 are the legal relationship between consumers and finance companies, namely financing agreements, so that if one party does not fulfill or violates the agreement, it will result in breach of promise/default and fiduciary installment (car) auction is not a consumer dispute issue.